Design of a Water Sprinkler System and Monitoring of Soil Moisture in Potato Cultivation of the Kledung Horticulture Seed Center based on the Internet of Things (IoT) - Eko Supriyanto; Endro Wasito; Abu Hasan; Dhea Ernanda; Karenza Balqis (Politeknik Negeri Semarang, 2020)
Potato is one of horticultural commodities that plays an important role to assure food security, mostly upper place such as plateau. Monitoring soil’s moisture and soil’s pH in potato plant tendance is the key point for good growth and development of potatoes. Soil moisture in a land is affected by the level of water contain in the soil. For that reason automatic monitoring system is needed to observe the land condition where the potato seedling is planted and a moisture control system that can ease the work. 40% to 70% of soil moisture is ideal for potatoes plant. The development of this design make use of wireless fidelity (wifi). This device keep the dampnes know less than 40%. If it’s less than 40%, the sensor will detected so the watering system will running and system will stop if reaching 70%. This design can monitor pH, temperature and humidity through the android application. With an accuracy level of the pH sensor for measuring 95.85% of acidity, the capacitive sensor for measuring soil moisture is 96.6% and DHT11 for measuring temperature and humidity at 99.75%.